2006
DOI: 10.2131/jts.31.1
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-Day Toxicity and One-Generation Reproduction Study in Rats Exposed to Allethrin-Based Liquid Mosquito Repellent

Abstract: -Rats exposed to liquid mosquito repellent (LMR) containing allethrin (3.6% w/w) 8-hrs/ day for a period of ninety days did not produce any signs of toxicity or death. Significant increases in relative weight of liver and adrenal in males, brain and thyroid in females were observed. No significant changes were noticed in clinical enzyme profile, gonadal enzymes and histopathology of vital organs except mild changes in the activities of liver and serum alkaline phosphates (ALP), testicular glucose-6-phosphate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Rats exposed to liquid mosquito repellent (LMR) containing allethrin (3.6% w/w) showed no significant effect on food consumption. [2] Lambda cyhalothrin also had no significant effect on water intake. [9] However, cypermethrin when given to white rabbits showed reduced feed and water intake in treated animals as compared to control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats exposed to liquid mosquito repellent (LMR) containing allethrin (3.6% w/w) showed no significant effect on food consumption. [2] Lambda cyhalothrin also had no significant effect on water intake. [9] However, cypermethrin when given to white rabbits showed reduced feed and water intake in treated animals as compared to control groups.…”
Section: Resultsmentioning
confidence: 99%
“…[1] They are most widely used group of pesticides due to their low toxicity to mammals, birds and insects. [2] Cypermethrin, a composite pyrethroid, is a broad-spectrum insecticide and fast acting neurotoxin with good contact and stomach action. [3] Consistent with its lipophilic nature, it has been found to accumulate in body fat, skin, liver, kidneys, adrenal glands, ovaries and brain.…”
Section: Introductionmentioning
confidence: 99%
“…The previous reports showed that permethrin (PM) was a highly toxic synthetic pyrethroid pesticide widely used in agriculture aquatic organisms and vector control programs (Vadhana et al, 2010;Fojut and Young, 2011;Srivastava et al, 2006). Reproductive toxic (Zhang et al, 2008), immunotoxic (Jin et al, 2010), neurotoxic (De Micco et al, 2010) and cardiotoxic (Vadhana et al, 2010) effects of PM were reported.…”
Section: Introductionmentioning
confidence: 99%
“…The histological features of the thyroid samples were examined. The thyroid body weight ratio was calculated as a relative thyroid weight [16].…”
Section: Animal Modelsmentioning
confidence: 99%